Sustainability of public financial management. Case study: implementation of Sustainable development goals in public budgeting in Ukraine - Pylypchuk Viktoriia (My University, 2023)
The Sustainable Development Goals1, adopted at the United Nations2 General Assembly on 25 September 2015, cover various challenges facing developing and developed countries. Like other UN member states, Ukraine has joined the global process of ensuring sustainable development. However, the outbreak of a full-scale war against Ukraine has put all of Ukraine's achievements at risk. At the same time, using the Goals in Ukraine's post-war recovery could be the key to ensuring not just reconstruction but complete modernisation based on the principle of "rebuilding better". This thesis aims to explore approaches to integrating the SDGs into national planning and budgetary processes. More specifically, it explores what strategy can be used to integrate the SDGs into the public budgeting process in Ukraine. The motivation to study the context of public budgeting stems from the extent of academic literature mainly focusing on the private sector's role in the global sustainable development agenda. However, successful implementation of the SDGs requires broad interdisciplinary coordination, good governance and large-scale funding. Improving budgeting and incorporating SDG into budget programs, appropriations, reports, and other elements of the budget cycle is an essential step toward achieving these sustainable development goals. The study reveals the current state of implementation of the SDGs in strategic and budgetary planning in Ukraine and examines the experience of several OECD countries. A combined institutional approach is the study's theoretical basis as it explains how changes in the budgeting process take place and why approaches are not homogeneous and universal. The empirical findings are based on an analysis of empirical data: secondary data as reports and accounts, and primary data from a questionnaire and structured interviews with 20 representatives of Ukrainian authorities and experts, and a semi-structured interview with a representative of the Norwegian government. The findings demonstrate that despite the repeated statements from the UN on the importance of including the SDGs in the budgeting process, there are not many countries yet that have announced the implementation of the SDGs in their public budgeting. The study illustrates that even in those countries which have formally announced budgeting according to the SDGs, these goals have not become transformative for the budgeting process but have been incorporated into the regular one. Despite the increasing emphasis on the significance of SDGs and their formal mention in the strategic documents, officials in Ukraine seem to prioritise maintaining the current state of affairs. Based on these setpoints, automatically adopting a SDG budgeting model from other countries is impractical. Finally, the current research results show that to combine formal (legislative) and informal institutional changes (actors' actions), significant shifts in institutional logic are required. In light of these key conclusions, the following contributions are derived. First, this thesis contributes to filling a research gap and complements the limited literature on SDG budgeting. Specifically, it illustrates the institutional changes that occur during the budgeting process with the implementation of SDGs and the role that actor logic plays. Moreover, the research findings bring some practical implications related to directions for developing an institutional framework for SDG budgeting in Ukraine.
Keywords: Agenda 2030; budget; budgeting process; institutional changes sustainability; sustainable development goals; SDG budgeting; SDGs